Kinetics of Nickel-Fulvate Reaction in Sewage Effluents Irrigated Soils - and A.P. Singh, Vipin Kumar, R.K. Prasad, B. Prasad (Journal of the Indian Society of Soil Science, 2014)
The kinetics of nickel-fulvate (Ni-FA) reaction with sewage effluents irrigated soils between 0 to 144 h conformed to first order reaction. As predicted by kinetic model, the kinetic constant for the loss of Ni from Ni-fulvate varied from 1105 to 1887 mol h-1 (av. 1424 mol h-1) at 15 0C, from 1179 to 1828 mol h-1 (av. 1555 mol h-1) at 30 0C and from 1175 to 2317 mol h-1 (av. 1709 mol h-1) at 45 0C. These results revealed that rate of Ni-fulvate reaction in soils increased with increasing temperature indicating rates of Ni-FA reaction were temperature dependent. The rate of loss of Ni from Ni-FA by competing ions was positively and significantly correlated with organic carbon (r = 0.512*). The half life of residence of Ni-FA reaction in soils ranged from 3.7×10-4 to 6.3×10-4 h (av. 4.98×10-4 h) at 15 0C, from 3.6×10-4 to 5.9×10-4 h (av. 4.53×10-4 h) at 30 0C and from 3.0×10-4 to 6.9×10-4 h (av. 4.55×10-4 h) at 45 0C. The half life time of residence of Ni-FA in soil decreased with increasing temperature. The average diffusion coefficient of Ni increased from 4.58×10-6 to 7.04×10-6 cm2 sec-1 with increasing temperature from 15 to 45 0C indicating that diffusion is temperature controlled reaction.